Analysis of financial Ratio for Predicting Profit Changes at PT. Indofood Sukses Makmur Tbk - Hartini; Chalid Imran Musa; Nurman; Romansyah Sahabuddin; Burhanuddin (Economics and Business Journal (ECBIS), 2023)
This study aims to test whether the variables Liquidity (CR), Solvency (DAR), and Profitability (ROA) have an influence on Profit Changes at PT. Indofood Sukses Makmur Tbk. The population in this study is all financial report data of PT. Indofood Sukses Makmur Tbk for the 2014-2021 period in each quarter, while the samples in this study are statements of financial position and profit/loss reports. The documentation technique is the data collection technique used. The collected data were analyzed using financial ratios which were then entered into the multiple linear regression equation. Based on the results of this analysis, it can be seen that partially the current ratio and debt to assets ratio do not have a significant effect on changes in earnings. These results are inconsistent with (H1) and (H2) which say the current ratio and debt to asset ratio partially have an influence on changes in earnings. It is also known that partially the return on assets has a significant effect on changes in earnings. These results are in accordance with (H3) which says return on assets has an influence on changes in earnings. From the results of this analysis it can also be seen that simultaneously the current ratio, debt to assets ratio, and return on assets do not have a significant effect on changes in earnings. This result is inconsistent with (H4) which states that the current ratio, debt to asset ratio, and return on assets simultaneously have an influence on changes in earnings.